2012
DOI: 10.1111/j.1600-0501.2012.02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate provisional restoration of single‐piece zirconia implants: a prospective case series – results after 24 months of clinical function

Abstract: Clinical and radiographic parameters demonstrated a 95% integration of immediately loaded zirconia single-piece implants. A long-term randomized-controlled clinical trial was initiated to confirm evidence of this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 55 publications
(110 reference statements)
5
97
0
Order By: Relevance
“…In addition to the peri implant evaluations, the adjacent teeth were frequently taken as references. In one investigation, solely a "healthy soft tissue" (Jung et al 2015) in the peri-implant area was described, whereas others found decreased bleeding and plaque indices in the course of the follow-ups (Kohal et al 2012;Kohal et al 2013;Payer et al 2013).…”
Section: Soft Tissue Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the peri implant evaluations, the adjacent teeth were frequently taken as references. In one investigation, solely a "healthy soft tissue" (Jung et al 2015) in the peri-implant area was described, whereas others found decreased bleeding and plaque indices in the course of the follow-ups (Kohal et al 2012;Kohal et al 2013;Payer et al 2013).…”
Section: Soft Tissue Parametersmentioning
confidence: 99%
“…Considering the available data exceeding one year of observation, an expected decrease of 0.05% per year afterwards was calculated (Figure 3). Most of the implant failures occurred in the early period after placement (Cannizzaro et al 2010;Grassi et al 2015;Jung et al 2015;Kohal et al 2012;Payer et al 2013;Spies et al 2015a). …”
Section: Implant Survival (Figure 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of participants in the studies ranged between 5 and 74. Eleven studies 1,3,4,23,24,26,27,[29][30][31][32] reported the mean age of participants, which was between 38.5 years and 62 years (age range 18 to 80). Ten studies 1,3,23,26-32 reported the percentage of female participants, which ranged between 6% and 57.5% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However loading forces emerge on the supramucosal part of the implant by mastication and tongue movements immediately after placement, and there is limited data on this topic. 28,29 Kohal et al reported 95.4% survival rate for one-piece zirconia implants for single-tooth replacement after 1 year which is comparable with titanium implants. 11 However, the radiographic bone loss after 1 year (>2 mm) was higher than titanium implants.…”
Section: Figurementioning
confidence: 89%